Application of mineral processing operations to the recovery of PVC and PET from plastic waste - Vásquez, Custodio (2001)
The present work deals with the proposed treatment scheme for the recovery of PVC and PET using mineral processing operations such as: size reduction. Separation by dense means, alkaline treatment and flotation. The results achieved at the laboratory level indicate that 95% of PVC and 97% of PET can be recovered from the selected sample of plastic containers collected in a residual sector of the city of Bucaramanga, Colombia.